Muscle oxygen desaturation is related to whole body VO2 during cross-country ski skating - Im, J.; Nioka, S.; Chance, B.; Rundell, K. W. (International Journal of Sports Medicine, 2001)
Previous research has demonstrated that blood flow and subsequent O2 desaturation (OD) in exercising muscle is related to the static component during exercise. In speed skating, increased OD is dissociated from whole body VO2 and heart rate (HR) when the skater increases the static component by 'sitting low'. This phenomenon was evaluated in cross-country skiers by manipulating speed and incline during treadmill roller skiing. Eight male cross-country skiers (22.4 +/- 3.2 yrs old) randomly performed constant incline- and constant speed-based protocols in which increased load was manipulated in five 4min stages by treadmill incline or speed change, respectively. A strong relationship (r = 0.83) was observed between VO2 and % OD while blood volume change (deltaBV) was minimal. Unexpectedly, no HR/ VO2 or HR/OD shifts were observed between protocols. The % OD response, in relation to blood lactate values, during submaximal exercise was very similar to that of VO2. The lack of an observed greater desaturation at higher inclines suggests that the expected static load may be attenuated by an increased contribution of poling. The strong relationship of % OD to whole body VO2 may be attributed to O2 dissociation in the capillary bed of the muscle to meet aerobic energy demand and is independent of blood flow dynamics during cross-country ski skating.